Membangun Loyalitas Pengguna Aplikasi Shopback Melalui Program Cashback dan Voucher Diskon - Abdullah, Pipit; Anggarawati, Sularsih (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
The aim of this research is to analyze customer loyalty through the cashback program and discount vouchers provided by the ShopBack application. Descriptive qualitative with survey design is the type of research used. The Shopback application acts as a research object. Interviews with 5 sources who used the ShopBack application were the primary data source used, while comprehensive observations of phenomena in the ShopBack application review feature on the AppStore and PlayStore from January to September 2023 were the secondary data source used. The research results show that cashback and discount vouchers have helped the ShopBack application increase customer loyalty. The ShopBack application has succeeded in creating an attractive online shopping ecosystem for its customers by combining strategy and customer data analysis. This effort can be a good example for other e-Payment applications that want to increase customer loyalty in the competitive digital era.